UMP ranked 301-400 in THE Impact Rankings - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 28 April 2022 - Universiti Malaysia Pahang (UMP) is ranked 301st-400th and 8th in Malaysia in the global impact rating Time Higher Education (THE Global Impact Ranking) announced on 27 April 2022.